Positive parenting for positive parents: HIV/AIDS, poverty, caregiver depression, child behavior, and parenting in South Africa - Lachman, J.; Cluver, L.; Boyes, Mark; Kuo, C.; Casale, M. (Routledge, 2014)
Families affected by HIV/AIDS in the developing world experience higher risks of psychosocial problems than nonaffected families. Positive parenting behavior may buffer against the negative impact of child AIDS-orphanhood and caregiver AIDS-sickness on child well-being. Although there is substantial literature regarding the predictors of parenting behavior in Western populations, there is insufficient evidence on HIV/AIDS as a risk factor for poor parenting in low- and middle-income countries. This paper examines the relationship between HIV/AIDS and positive parenting by comparing HIV/AIDS-affected and nonaffected caregiver-child dyads (n=2477) from a cross-sectional survey in KwaZulu-Natal, South Africa (27.7% AIDS-ill caregivers; 7.4% child AIDS-orphanhood). Multiple mediation analyses tested an ecological model with poverty, caregiver depression, perceived social support, and child behavior problems as potential mediators of the association of HIV/AIDS with positive parenting. Results indicate that familial HIV/AIDS's association to reduced positive parenting was consistent with mediation by poverty, caregiver depression, and child behavior problems. Parenting interventions that situate positive parenting within a wider ecological framework by improving child behavior problems and caregiver depression may buffer against risks for poor child mental and physical health outcomes in families affected by HIV/AIDS and poverty.